(دون)في التراث اللغوي والنحوي (University of Mosul-college of Basic Education, 2011)
يتحدث هذا البحث الموسوم بـ " (دون) في التراث اللغوي والنحوي " عن فكرة تنطلق من ان بيان معنى اللفظ منفرداً قبل دخوله في نسج التأليف مهم ، لأنه لا يمكن أن نهمل جانب المدلول اللغوي في الألفاظ المنفردة ، بيد أن الاقتصار عليه لا يحدد الدلالة القطعية لان الكلمة في هذا الإطار تكون ممثلة لعدة احتمالات واختيارات دلالية ، لذا فالقول بأن مادة الكلمة وحدها تحدد المعنى وبيانه قول مبالغ فيه وكذا اذا قيل السياق وحده يحدد المعنى بل ان دلالة اللفظ وبيانه تتحدد بمادة الكلمة والسياق الوارد فيه مجتمعين . لذا فالبحث قد تناول دلالات (دون) في الأنساق التي وردت في كلام العرب والتي لا تتحدد دلالتها إلا من خلال الاستعمال وذلك عند دخولها في سياقات تركيبية تمنحها أبعاداً إضافية . This study, entitled "(Doon) in the Linguistic and Grammatical Heritage" tackles the idea which denotes that the statement of the expression separately before it becomes connected with the context is very important, because the aspect of the linguistic meaning in the separate expressions can not be neglected. Morever , the confinement to it doesn't refer to the absolute denotation because a word in this framework represents several semantic probabilities and choices. So, considering that the sole origin of the word indicates the meaning and the denotation is exaggerated Similarly, if we say that the context does that by itself only. The denotation and the statement of the expression is limited by the origin of the word and the context altogether. So, the study tackles the denotations of the word (doon) from the patterns of the Arab speech whose denotations cannot be identified without the usage in constructive contexts that give them additional dimensions المقدمة: